Metaphorical Perceptions of Gifted Students towards Mathematics and Science Concepts - Duygu Özdemir, Ayşegül Kınık Topalsan (Educational Process: International Journal)
Background/purpose – Understanding gifted students’ perceptions by means of metaphors, carefully examining and interpreting them may help to guide the organization of training programs and the differentiation of educational content for gifted students. This study aims to reveal the perceptions of gifted students regarding science and mathematics concepts as well school math, school science, scientist, experiments, and problem-solving perceptions by examining students’ metaphors.